A qualitative exploration of cultural safety in nursing from the perspectives of Advanced Practice Nurses: meaning, barriers, and prospects - Jacqueline Pirhofer; Johannes Bükki; Mojtaba Vaismoradi; Manela Glarcher; Piret Paal (BMC, 2022)
Abstract Background Cultural safety requires healthcare professionals and organisations to improve healthcare, facilitate patient access to healthcare, and achieve equity within the workforce. Methods This ethnomethodological study, which consisted of two phases, explored the concept of cultural safety from the perspective of Advanced Practice Nurses. Semi-structured interviews and the nominal group technique were used to prioritise challenges related to cultural safety, identify barriers to clinical practise and assess educational needs. The data collected was subjected to thematic analysis. Results Nurses working in Austria, Germany and Switzerland were recruited (N = 29). Accordingly, the phenomenon of cultural safety in health care is not generally known and there is little prior knowledge about it. The most frequently discussed themes were communication difficulties, lack of knowledge, the treatment of people with insufficient language skills and expectations of treatment goals and outcomes, which can lead to conflicts and accusations of unequal treatment due to diverse cultural backgrounds. Conclusion Diverse cultures are encountered in German-speaking healthcare settings. Cultural safety is also about healthcare staff, as nurses with different socialisations encounter prejudice, discrimination and racism. Although the issue of power was not discussed, academic nurses were willing to make an effort to change. Only a minority were aware that lasting change requires challenging one's own cultural structures and adapted behaviours, rather than pushing for the mere acquisition of cultural competence. Organisations were encouraged to introduce self-reflection sessions and provide better access to translation services to improve equity and support nurses.